Study to detect infection and diagnose chorioamnionitis to aid in management of cases of preterm premature rupture of membranes in a tertiary care centre of Jharkhand - Dutta, Indrani; Horo, Usha Madhulika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The present study undertaken is to identify the risk factors causing Preterm premature rupture of membranes (pPROM) and to study fetal and maternal outcome associated with pPROM, to diagnose and manage chorioamnionitis associated with pPROM and to evaluate levels of C reactive protein (CRP). Methods: This study was conducted in the department of obstetrics and gynaecology, Rajendra institute of medical sciences from March 2019 to February 2020.50 cases of confirmed preterm premature rupture of membrane before 35 weeks of pregnancy were taken as cases and 50 cases of normal pregnancy (28-40 weeks) were taken as controls. Results: Highest incidence of premature rupture of membrane was among 20–25-year (68%) age groups. Incidence of premature rupture of membrane was more in low socioeconomic status (72%). Maximum incidence of premature rupture of membrane in 31-33 weeks gestational age (52%). Most cases of premature rupture of membrane in 24–48-hour group (38%). Most of study group (90%) and control group (80%) delivered by vaginal route. 11 study cases with clinical chorioamnionitis had elevated CRP (43.5 mg/l). One presented with clinical chorioamnionitis. CRP was most sensitive (92%). Total maternal morbidity was due to puerperal pyrexia (22%). Four patients with neonatal sepsis had CRP>6 mg/l. CRP and presence of polymorphs in gastric aspirate have 100% association with septicemia in neonates. Conclusions: Preterm premature rupture of membrane can be associated with adverse foetal and maternal outcome if immediate measures are not taken.